PENGEMBANGAN LAGU RELIGI BERBASIS WORDWALL UNTUK PEMBELAJARAN KARAKTER SISWA KELAS 1 SDN 3 CIBEUREUM - Dea Siti Wahdiati; Nunu Nurfirdaus; Dudung Abdu Salam (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop a learning medium in the form of religious songs based on the Wordwall platform for character education in Pancasila Education, with the goal of instilling character values in first-grade students at SDN 3 Cibeureum. The research employed a Research and Development (R&D) approach, using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. Observations and questionnaires revealed that first-grade students face character-related issues such as discipline, peace-loving attitudes, and social awareness. Initial data showed that the average character assessment score was 59.7%, categorized as